The Effects of Reading Test, Writing Skills and Learning Motivation Toward Learning Outcome of Bahasa Indonesia Subject in Students in Primary School (Journal of Primary Education, 2019)
Literacy culture has not been applied significantly in Bahasa Indonesia subjects in primary school. The purpose of this study was to examine the effect of reading test with Progress in International Reading Literacy Study (PIRLS) standard, writing skill, learning motivation, and learning outcome of Bahasa Indonesia partially; and determine the magnitude of the effect of reading tests with PIRLS standards, writing skills, through mediation of learning motivation toward Bahasa Indonesia learning outcomes. This research was a quantitative research of correlational type. The study was conducted at SD Gugus Sawojajar UPTD Pendidikan Banyumanik Sub-District of Semarang, involving 125 students of grade IV. Data collections used were documentation, tests and questionnaires. Methods of data analysis used descriptive and inferential analysis. The result of the research shows that there is influence of reading test with PIRLS standard toward learning outcome of Bahasa Indonesia subjects is 0.505 (medium category); the effect of writing skill on learning outcome of Bahasa Indonesia subjects is 0.676 (high category); the influence of learning motivation on learning outcome of Bahasa Indonesia subjects is 0.450 (medium category); the effect of reading test with PIRLS standard on learning outcome of Bahasa Indonesia subjects is motivated by learning motivation of 0.597 (medium category); and the influence of writing skills on learning outcome of Bahasa Indonesia mediated learning motivation is 0.694 (high category). The results of the study are expected to make effective in learning Bahasa Indonesia and get satisfactory learning outcomes.